The Concept Of Mimicry In The God Of Small Things - Sattar Hashim; Sarmad Alahmad (TRANSBAHASA, 2023)
This study intends to examine the impact of mimicry on India’s citizens in The God of Small Things by Arundhati Roy, with a focus on the Post-colonial approach. The significance of this study is dedicated to present the overlapping influence of both the East-West, in the customs, language, garments, and extended to incorporate their manners. Thus, the imitation in aforementioned text is reflected and explored throughout the characters’ demeanors within the remarkable framework of Post-colonial theory. The findings of the study indicate that there are several mimicking hints in the novel, which raises the topic of identity throughout the lifestyles of India’s citizens.